The factor influences to do exercise during movement control Order among UiTM Perlis students / Nurul Fathin Nabella Ahmad Zamri - Ahmad Zamri, Nurul Fathin Nabella (2021)
Exercise is involves the things that were meant for health or preparation rather than something that was part of our everyday routine. However, due to the pandemic issues which is COVID – 19, Malaysia government had announced the Movement Control Order (MCO) where people a need to stay at home and prohibited to do any exercise such going to recreational park, going for gym to workout, mass gathering or any outdoor activity that exposed to the external environment. To date, there was limited study on factor influences to do exercise during MCO among UiTM Perlis students. Therefore, the purpose of this study is to investigate the factors influence to do exercise during MCO among UiTM Perlis students. A total of 389 respondents among UiTM Perlis were set up in WhatsApp to answer International Physical Activity questionnaire by using Google Form. The result of this study indicate that there was significant different on external factors influence to do exercise during MCO (p <0.05) observed among UiTM Perlis students. Besides, the result prove that there was a significant different on external factor due to the lack of time was one of the most important external factor for exercise that affect people to do exercise. Therefore, the factors influence to do exercise during MCO among UiTM Perlis students was internal factor due to the key reasons for the students do exercise were improving the look, improving health and losing weight whereas the factor of internal.